Building Biology Criteria and Architectural Design - Ece, Nurgül (Birkhäuser, 2018)
Health and environmental compatibility are key topics in contemporary society. The book shows how the built environment can be aesthetically pleasing, modern and, at the same time, healthy and environmentally friendly. It makes the link between architecture as a design task and a building biology approach to design. Building biology teaches us about the holistic interaction between people and their built environment. It combines building culture with ecology and disciplines such as chemistry, biology, geology, and psychology. Using the building of the Institute of Building Biology + Sustainability (IBN) as a model, building biology criteria and approaches are explained in detail. Numerous additional current projects illustrate how these are implemented in responsible, healthy, and hence sustainable architecture.